ANALISIS KEMAMPUAN NUMERASI SISWA SMPN 18 SAMARINDA DALAM MENYELESAIKAN SOAL AKM BERDASARKAN GAYA KOGNITIF - Prahesti, Selvia Shinta; Asyril, Asyril; Rizki, Nanda Arista (Universitas Bhinneka PGRI, 2025)
The study aimed to describe the numeracy skills of SMPN 18 Samarinda students in working on AKM (Minimum Competency Assessment) questions based on FI (Field Independent) and FD (Field Dependent) cognitive styles. The study used qualitative research methods. The subjects were 30 students of class VIII of SMP Negeri 18 Samarinda, while the object of the study was the students' numeracy skills in solving AKM questions based on cognitive styles. The data collection techniques used included tests and interviews. The data analysis technique was conducted descriptively by determining the average score of the AKM test results. The results indicated that at the cognitive level of understanding, students with FI and FD cognitive styles were able to calculate and solve cognitive questions. At the cognitive level of application, students with FI and FD cognitive styles were able to apply and choose strategies for solving AKM questions. At the cognitive level of reasoning, students with FI cognitive style were able to present and evaluate in solving cognitive questions, while students with FD cognitive style were only able to present. Suggestions for future research using different materials or referring to this study as a consideration for improving learning.